Contributions to the debate about abortion in chile: rights, gender and bioethics - Dides C., Claudia (Acta Bioethica, 2006)
This paper is a reflexive essay about the abortion problem in Chile, considering the current historical context as well as a critical approach from the gender and bioethical perspective. The analysis has been organized in three tracks: the abortion context in Chile in relation to the human rights, the changes in privacy and the contribution of bioethics and gender perspective to this debate. Finally, for reflection, some current tensions as well as questions for future studies are presented.